Academic Senate Minutes 2003-05-08 - Academic Senate:::::::::
Report from Chair. Agenda amended and approved. Consent items accepted: Accounting Certificate, B.A. in Art History. Reports from Provost, Associated Student President, APC, EPC, FSAC, SAC. B. S. in Engineering Science first reading. Guest speaker Vicki Vidak-Martinez, Mayor of Rohnert Park. Report from Academic Council on International Programs representative, Elizabeth Martinez. Grade Posting item added to agenda resulted in Motion: RESOLVED that the Academic Senate of Sonoma State University recommends to the administration of Sonoma State that faculty be "requested" instead of "required" to use PeopleSoft software to enter their grades for the Spring semester 2003. The Senate further recommends that faculty have the choice to use PeopleSoft to post their grades or continue the past practice of posting grades to a roster. Approved, 20 in favor, 3 abstentions.